Evaluation of transit lines plan - Cenek, Juraj (Univerzita Pardubice, 2012)
The plan of mass transport or transit lines is a vital part of an organisation of public transportation services. An optimisation of the plan can improve the service either by reducing the operational costs or by improving of service quality. Three subjects interact in the problem namely state or local administration, transport companies and citizens. The plan optimisation should find the best compromise to satisfy interests of all actors. A relevant criterion must be defined to find the best solution. Calculating passenger criterion values must include model of passenger’s decision.
Keywords: transportation planning; transit lines; costs criteria; service quality; optimization